Quirino lifesprings a wellness centre of development - Lagmay, Arlo Jake L. (Publication of Engineering & Architecture Researches, 2014)
"Put up a resort. Amuse people so we can earn money." This is how a typical developer thinks or what he would say the potential scenic spots in the province are meant to be utilized. Ending this type of marketing strategy, the Cua administration is now spearheading the development of the whole territory into natural real tourist spots to be fully enjoyed by everyone. The government is making it sure visitors will be awed by the attractions these spots can offer.